The situation of Venezuelan migrants in Norte de Santander - Quintero Bayona, Belén Torcoroma; Pacheco Sánchez, Carlos Alberto; Vargas Prieto, Amanda (Cooperativismo & Desarrollo, 2021)
Since the 1980s, the political situation in Venezuela has generated a national crisis that has been reflected in the migration of more than 5% of the population, mostly in Colombia and Peru. This situation presents two systematic problems for Colombia. The first refers to the absence of updated data because there is no infrastructure to collect the necessary information. The second is the long extension of the Colombian-Venezuelan border, particularly finding that in Norte de Santander is the largest number of Venezuelans in Colombia. For this reason, the objective of this research is to study the situation of migrant Venezuelans in this department. To achieve this objective, a qualitative methodology was proposed, based on a unique case study in the municipality of Ocaña. Where observation, documentary review and surveys were carried out, which analyzed the characterization of the population.